Pengaruh Komitmen Organisasi dan Motivasi Kerja terhadap Organizational Citizenship Behavior melalui Kepuasan Kerja sebagai Variabel Intervening pada PT Roda Maju Bahagia - Arifiani, Zefi Nafira; Widhiastuti, Hardani; Nunik Kusnilawati (Universitas Semarang, 2024)
Employees who have loyalty and commitment will try their best to achieve goals. When employees feel satisfied with the work they do, then employees work optimally in completing their work. Individuals who have high work motivation will bring up OCB behavior. This study aims to determine whether there is an influence of Organizational Commitment and Work Motivation on Organizational Citizenship Behavior Through Job Satisfaction as Intervening Variables at PT RMB. This study used quantitative methods with random sampling techniques. The population in this study were PT RMB employees, totaling 183 people. The results of the study found that there was a positive and significant effect between job satisfaction and OCB at PT RMB. There is a positive and significant influence between organizational commitment and job satisfaction at PT RMB. The mindset variable has a significant effect on job satisfaction. There is no significant influence between Organizational Commitment and OCB on employees at PT RMB. There is a positive and significant influence between organizational commitment and job satisfaction at PT RMB. There is no significant effect between work motivation and OCB on employees at PT RMB.